Aging time affects color stability and sensory properties of ground beef patties adjusted to a Similar Fat Composition by Combining Subprimals from the Chuck Roll and Knuckle - Brandi D. Cleveland; Robert S. McEwan; John A. Unruh; C. M. Garner; Sally L. Stroda (Kansas Agricultural Experiment Station Research Reports, 2014)
Palatability traits of flavor, juiciness, and tenderness are associated with consumer satisfaction. Although grinding offers an opportunity to mechanically minimize differences in tenderness, muscle source and product quality may still affect the sensory properties of ground beef. The objective of this study was to determine the effects of two quality grades (Premium Choice and Select) and vacuum storage aging time (7, 21, and 42 days) before processing on ground beef patty display color from chuck roll and knuckle subprimals combined to obtain a common percentage of fat.
Keywords: Cattlemen' s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen' s Day; Beef; Ground beef; Fat levels; Color; Vacuum storage; Aging time